1991
DOI: 10.1073/pnas.88.8.2984
|View full text |Cite
|
Sign up to set email alerts
|

Stable three-stranded DNA made by RecA protein.

Abstract: When RecA protein, in the form of a nucleoprotein filament containing circular single-stranded DNA (plus strand only), reacts with homologous linear duplex DNA, a directional transfer ensues of a strand from the duplex DNA to the nucleoprotein lament, resulting in the displacement of the linear plus strand in the 5' to 3' direction. The initial homologous synapsis, however, can occur at either end of the duplex DNA, or anywhere in between, and when homology is restricted to different regions of the duplex DNA,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
51
1

Year Published

1992
1992
2007
2007

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(55 citation statements)
references
References 32 publications
3
51
1
Order By: Relevance
“…The experiments in this discussion employed short ssDNA with homology restricted to the middle of the linear target dsDNA, whereas Hsieh and Rao and their coworkers used a long circular ssDNA and a linear dsDNA in which the homology (ranging from 38-56 bp in length in one study to a few kilobases in another) is restricted to the 5' end of the recipient strand of the dsDNA. When the homology was restricted to the middle or the other end of the dsDNA, the stable, protein-free, three-stranded structure was not detected (Rao et al 1991), in agreement with the results reported here. If the putative triplex DNA involving non-WatsonCrick base-pairing is one of the stable intermediates of DNA synapsis as proposed (Hsieh et al 1990;Rao et al 1991), it will be interesting to investigate why the efficient formation and/or stability of this structure require a particular end of DNA, as this has been unprecedented up to now in canonical DNA triple helices.…”
Section: How Does Reca Recognize a Homology Between Ssdna And Dsdna?supporting
confidence: 82%
See 2 more Smart Citations
“…The experiments in this discussion employed short ssDNA with homology restricted to the middle of the linear target dsDNA, whereas Hsieh and Rao and their coworkers used a long circular ssDNA and a linear dsDNA in which the homology (ranging from 38-56 bp in length in one study to a few kilobases in another) is restricted to the 5' end of the recipient strand of the dsDNA. When the homology was restricted to the middle or the other end of the dsDNA, the stable, protein-free, three-stranded structure was not detected (Rao et al 1991), in agreement with the results reported here. If the putative triplex DNA involving non-WatsonCrick base-pairing is one of the stable intermediates of DNA synapsis as proposed (Hsieh et al 1990;Rao et al 1991), it will be interesting to investigate why the efficient formation and/or stability of this structure require a particular end of DNA, as this has been unprecedented up to now in canonical DNA triple helices.…”
Section: How Does Reca Recognize a Homology Between Ssdna And Dsdna?supporting
confidence: 82%
“…These results are not only consistent with the DMS-reactivity data reported here but also argue against the view that the process of homology recognition involves an intermediate in which N-7 of G plays a critical role. The results in this discussion are not necessarily at odds with those reported by Hsieh et al (1990) and Rao et al (1991), who found a stable DNA structure after the removal of RecA in which all three strands appear to be somehow juxtaposed. The apparently different experimental outcome may be simply due to differences in experimental conditions, most notably the combination of DNA substrates used.…”
Section: How Does Reca Recognize a Homology Between Ssdna And Dsdna?contrasting
confidence: 56%
See 1 more Smart Citation
“…Second, thymines within the synaptic complex, but close to the reactive flank, are hyper-reactive in all three strands. This asymmetry in modification of two flanking regions probably reflects the polarity of presynaptic filament assembly and subsequent strand exchange (Konforti & Davis 1990Dutreix et al 1991).…”
Section: Modification Of the Synaptic Complexes With Potassium Permanmentioning
confidence: 99%
“…RecA protein is capable of directly recognizing specific base sequences in double-stranded DNA molecules and is known to form a triple-stranded structure with a complementary oligonucleotide, but the triple-stranded structure is quite unstable, particularly when RecA protein is removed (West et al 1981;Rao et al 1991. Attempts have been made to make the structure stable enough to withstand various subsequent manipulations (Fujiwara et al 1998a,b;Potaman et al 2002;Roulon et al 2002).…”
mentioning
confidence: 99%